Implementation of Early Detection of Mental Nursing in the Community - Pragholapati, Andria; Nur Anna, A; Ratna E, Suci; Nompo, Rifki Sakinah; Farkhah, Laeli; Hadiansyah, Tantan; Eryanto, Bambang; Susanto, Wigyo (Universitas Pendidikan Indonesia, 2021)
Strengthening quality primary health care efforts, especially through increasing health insurance, increasing access and quality of basic and referral health services supported by strengthening the health system and increasing health financing. Policies related to early detection in public mental health preventive efforts are implied in the direction of Ministry of Health policies, namely Strengthening primary health care, Implementation of the Continuum of Care Approach, and Health Risk-Based Interventions.